Pengembangan Lembar Aktivitas Matematika Berorientasi Pendekatan Saintifik - Indriani, Novia; Pamungkas, Aan Subhan; Alamsyah, Trian Pamungkas (Desimal: Jurnal Matematika, 2019)
This research aims to develop mathematics student activity sheets on cube and rectangle box volume material, to determine the quality of mathematicsl activity sheets developed and to find out the user's response to mathematics activity sheets, and to understand students' understanding after using a sheet of mathematics activity. The development research method used in this study refers to the research design of the 4D model developed by Thiagarajan which consists of 4 stages of development namely Define, Design, Develop, and Disseminate. The subjects of this study were 30 fifth grade students at Panancangan Elementary School 2. The results of the study were (1) the average level of feasibility of the mathematics activity sheet reached 84.6% which was included in the category of "very feasible", obtain an average percentage of 97% which is included in the category of "very good", (3) the teacher's response to the sheet of mathematics activity gets an average percentage of 83% which falls into the category of "very good" and (4) understanding test students obtain an average value of 86.03 which shows students' understanding in the "very good" category so that it can be concluded that the mathematics activity sheet was successfully developed into a better teaching material because it has been prepared according to the design and is able to provide learning benefits.